Overcoming Marginalization and Disengagement in Adult Education: Adult Educators’ Contributions to the Scholarship of Engagement - Richard Kiely; Lorilee Sandmann; Susan Bracken (Adult Education Research Conference, 2006)
As adult educators whose work has had an impact on shaping the discourse on scholarly engagement, service-learning and community-based education, we will describe our different approaches to this movement and share our diverse practical experiences fostering greater community engagement in the areas of teaching, research and service.
Keywords: Scholarship of engagement; service learning; community-based research